2020
DOI: 10.1101/2020.09.25.313676
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Host immune responses after suprachoroidal delivery of AAV8 in nonhuman primate eyes

Abstract: The suprachoroid is a potential space located between the sclera and choroid of the eye which provides a novel route for ocular drug or viral vector delivery. Suprachoroidal injection of AAV8 using transscleral microneedles enables widespread transgene expression in eyes of nonhuman primates, but may cause intraocular inflammation. We characterized the host humoral and cellular immune responses after suprachoroidal delivery of AAV8 expressing green fluorescent protein (GFP) in rhesus macaques, and found that i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…The loss in transgene expression was attributed to chorioretinal infiltration of inflammatory cells which was accompanied by greater humoral and cellular responses to the GFP transgene, whereas intravitreal injection of the same vector and dose produced minimal transgene expression but greater sequestration to the spleen and stronger antibody responses to the AAV8 capsid. 86 Interestingly, GFP expression after suprachoroidal vector delivery appears to persist in scleral fibroblasts at month 3. Together, these studies suggest that the greater trabecular outflow of viral vectors from the vitreous cavity to the bloodstream and spleen can trigger stronger host immune responses to the AAV capsid, compared with the slower uveoscleral outflow of virus from the suprachoroidal space.…”
Section: Route Of Administration and Biodistributionmentioning
confidence: 99%
“…The loss in transgene expression was attributed to chorioretinal infiltration of inflammatory cells which was accompanied by greater humoral and cellular responses to the GFP transgene, whereas intravitreal injection of the same vector and dose produced minimal transgene expression but greater sequestration to the spleen and stronger antibody responses to the AAV8 capsid. 86 Interestingly, GFP expression after suprachoroidal vector delivery appears to persist in scleral fibroblasts at month 3. Together, these studies suggest that the greater trabecular outflow of viral vectors from the vitreous cavity to the bloodstream and spleen can trigger stronger host immune responses to the AAV capsid, compared with the slower uveoscleral outflow of virus from the suprachoroidal space.…”
Section: Route Of Administration and Biodistributionmentioning
confidence: 99%
“…The potential of SC gene therapies using marker genes, such as green fluorescent proteins (GFP) and luciferase, has been studied preclinically [ 80 , 81 , 82 ]. Briefly, multiple animal studies have demonstrated proof of concept with GFP expression after SC injections of adeno-associated viral vector (AAV) and nonviral vectors expressing GFP [ 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ]. In addition, the application of nanoparticle systems to deliver drugs or gene therapy into the SCS may further enhance therapeutic potential by optimizing for durability or particle spread [ 91 , 92 ].…”
Section: Viral and Nonviral Gene Therapiesmentioning
confidence: 99%
“…Yiu et al and Chung et al [ 93 , 95 ] reported a lower systemic humoral immune response with SC AAV8, compared to IVT AAV8; however, intraocular inflammation was more evident with AAV8 delivered to the SCS, compared to the subretinal space. Furthermore, there was a decreased transgene expression after 2 and 3 months that was hypothesized to be due to cellular damage and phagocytic activity related to the increased local inflammation.…”
Section: Advanced Therapiesmentioning
confidence: 99%